2007
DOI: 10.1002/art.22306
|View full text |Cite
|
Sign up to set email alerts
|

Binding of antiphospholipid antibodies to discontinuous epitopes on domain I of human β2‐glycoprotein I: Mutation studies including residues R39 to R43

Abstract: Objective. Pathogenic antiphospholipid antibodies (aPL) bind the self antigen N-terminal domain (domain I) of ␤ 2 -glycoprotein I (␤ 2 GPI), with residues G40-R43 being important. However, peptides homologous to other regions of domain I have also been shown to bind aPL. Furthermore, there are no published reports of the effects of altering R39, which has greater surface exposure than the G40-R43 residues.Methods. We used a novel, efficient method of production and purification of human domain I by Escherichia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(146 citation statements)
references
References 44 publications
7
138
0
Order By: Relevance
“…To identify the target epitope of MBB2, recombinant single domains of the b2GPI protein were used, and, testing 4 of the 5 domains, the antibody was shown to bind to the DI domain ( Figure 1B). The binding of MBB2 to DI was confirmed by Dr Michael Mahler (INOVA Diagnostics, San Diego, CA) using a novel solid phase chemiluminescent assay (BioFlash; INOVA Diagnostics) 29 and by Dr Anisur Rahman using solid phase-bound recombinant DI (described in Ioannou et al 30 ). To determine whether MBB2 interacts with cell-bound b2GPI, HUVECs and BeWo cells were exposed to purified b2GPI to allow surface binding of the protein and subsequently incubated with the scFv-Fc.…”
Section: Resultsmentioning
confidence: 95%
“…To identify the target epitope of MBB2, recombinant single domains of the b2GPI protein were used, and, testing 4 of the 5 domains, the antibody was shown to bind to the DI domain ( Figure 1B). The binding of MBB2 to DI was confirmed by Dr Michael Mahler (INOVA Diagnostics, San Diego, CA) using a novel solid phase chemiluminescent assay (BioFlash; INOVA Diagnostics) 29 and by Dr Anisur Rahman using solid phase-bound recombinant DI (described in Ioannou et al 30 ). To determine whether MBB2 interacts with cell-bound b2GPI, HUVECs and BeWo cells were exposed to purified b2GPI to allow surface binding of the protein and subsequently incubated with the scFv-Fc.…”
Section: Resultsmentioning
confidence: 95%
“…4,7 Mutagenesis studies indicate that the antigenic epitope of b2GpI in DmI is discontinuous in nature and comprises the amino acid residues Asp8 and Asp9, the Arg39-Arg43 segment, and the Domain I-II interlinker region. 7,16,17 Whether anti-b2GpI aAbs directly bind to a constitutively expressed epitope of b2GpI in DmI or to a cryptic epitope that becomes exposed in DmI only after b2GpI binds to negatively charged surfaces has been the subject of a lengthy debate. 18 Multiple mechanisms have been proposed for explaining the clinical manifestations of APS, including (1) complement activation, (2) dysregulated activation of platelets, endothelial cells, and monocytes, (3) disruption of the interactions of anticoagulant factors (i.e., activated protein C and annexin A5), (4) inhibition of fibrinolysis, and (5) inhibition of thrombin-mediated activation of Factor XI.…”
Section: Introductionmentioning
confidence: 99%
“…We, among others, have shown that an epitope within domain I of b2-glycoprotein I (b2GPI) is responsible for binding thrombosis related antibodies. [5][6][7][8] Furthermore we have shown that this epitope is only exposed when b2GPI changes from its native conformation into an active conformation able to bind certain types of antibodies, antibodies with affinity towards epitope glycine40-arginine43 (G40-R43) on domain I. 9 Interestingly we found that this population of antibodies is highly associated with thrombosis whilst antibodies with affinity towards other epitopes are not.…”
Section: Introductionmentioning
confidence: 81%